Crowd reception influences avoidance behavior during football penalty-kicks, but you wouldn't know it: A retrospective analysis of professional games. (July 2022) - Park, S.H.; Uiga, L.; Masters, R.S.W.
Abstract: For most soccer players, penalty-kicks are unpleasantly valenced, but the extent to which intensity of emotions affects their decision-making is unclear. We hypothesized that a hostile crowd raises emotional intensity more than a supportive crowd during penalty-kicks, which causes players to make avoidance based decisions more often in the presence of a hostile crowd. We sourced video footage of penalty-kicks during professional games between 2000 and 2005 (N = 91), during which the goalkeeper was marginally off-center (1.6%–3.0%) or obviously off-center (>3.0%). Taking the easiest option is a marker of avoidance behavior, so we analysed the proportion of penalty-kicks directed towards the larger side of the goal. Players kicked towards the larger side more often in front of a hostile crowd than a supportive crowd, but only when the goalkeeper was marginally off-center. The findings suggest that in the high-pressure environment of penalty-kicks, emotional intensity moderates the decisions that kickers make, without their awareness. Highlights: Examined the effect of hostile and supportive crowds on soccer penalty-kick behavior. Avoidance behavior was greater when facing a hostile crowd, but only when the goalkeeper was imperceptibly off-center. A hostile crowd may promote pre-attentive processing, which facilitates detection of subtle differences in space.